2010
DOI: 10.1128/cvi.00009-10
|View full text |Cite|
|
Sign up to set email alerts
|

HIV-1 Reactivation Induced by the Periodontal Pathogens Fusobacterium nucleatum and Porphyromonas gingivalis Involves Toll-Like Receptor 4 and 9 Activation in Monocytes/Macrophages

Abstract: Although oral coinfections (e.g., periodontal disease) are highly prevalent in human immunodeficiency virus type 1-positive (HIV-1 ؉ ) patients and appear to positively correlate with viral load levels, the potential for oral bacteria to induce HIV-1 reactivation in latently infected cells has received little attention. We showed that HIV-1 long terminal repeat (LTR) promoter activation can be induced by periodontopathogens in monocytes/ macrophages; nevertheless, the mechanisms involved in this response remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 80 publications
0
30
0
Order By: Relevance
“…Endosomal TLR9 can recognize certain types of bacterial DNA (unmethylated CpG DNA), which results in the production of proinflammatory mediators such as TNF-␣ and iNOS/NO by macrophages (30). A previous study revealed that bacterial DNA from F. nucleatum can lead to TLR9 activation in monocytes (8). In addition, BMDMs used in this study highly express the TLR9 gene compared with alveolar and peritoneal macrophages, and CpG oligodeoxynucleotide (ODN) induces the production of cytokines (IL-6, TNF-␣, and IL-12p40) in BMDMs (31).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Endosomal TLR9 can recognize certain types of bacterial DNA (unmethylated CpG DNA), which results in the production of proinflammatory mediators such as TNF-␣ and iNOS/NO by macrophages (30). A previous study revealed that bacterial DNA from F. nucleatum can lead to TLR9 activation in monocytes (8). In addition, BMDMs used in this study highly express the TLR9 gene compared with alveolar and peritoneal macrophages, and CpG oligodeoxynucleotide (ODN) induces the production of cytokines (IL-6, TNF-␣, and IL-12p40) in BMDMs (31).…”
Section: Discussionmentioning
confidence: 96%
“…TLR9 deficiency led to decreased production of tumor necrosis factor alpha (TNF-␣) in group B Streptococcus (GBS)-infected macrophages (7). Although it is known that F. nucleatum infection elicits TLR9 activation in monocytes (8), the role of endosomal TLRs in the immune response of macrophages against periodontal bacteria has yet to be clearly elucidated. Therefore, in the present study, we sought to identify TLR signaling-mediated immune responses in macrophages against the periodontal pathogens F. nucleatum and A. actinomycetemcomitans.…”
mentioning
confidence: 99%
“…[30, 31] We and others have shown that activation of transcription factors, such as NFkB upon Toll-like receptor engagement by bacteria, appears to play a critical role in pathogen-induced HIV-1 promoter activation from latently infected cells. [23, 32] Oral commensals are the predominant species at the oral mucosa and can be similarly recognized by TLRs enhancing activation of host cell transcription factors involved in HIV-1LTR positive regulation such as NFkB. [33, 34] Whether or not these bacteria induce HIV-1LTR activation remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…[19-21] Bacterial extracts from each microorganism were obtained as we have previously reported. [22, 23] Briefly, 5 colonies grown on blood agar plates were placed into 25 ml of corresponding broth and incubated for 24h. Then, bacterial cultures were transferred into 500 ml of the same broth, and incubated under the same conditions for 24h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation